Business continuity planning in visiting nurse stations in Japan: A nationwide cross-sectional study - Sato, Jun; Ishida, Chie; Iguchi, Aya; Kanno, Taro; Sato, Taichi; Nishida, Shiho; Kanesaka, Takayuki; Okada, Risa; Kawaguchi, Kanako; Horiike, Ryo (International journal of disaster risk reduction, 2025)
Ensuring continuity of home-based healthcare services during disasters is a critical challenge in disaster-prone countries such as Japan. Visiting Nurse Stations (VNSs) provide essential care to homebound individuals, yet many remain unprepared for emergencies. This study examined the status of Business Continuity Planning (BCP) among VNSs in Japan during March–April 2023 and identified factors associated with its implementation. We conducted a cross-sectional survey using stratified random sampling, collecting data via postal and online questionnaires. Analyses included descriptive statistics, weighted estimates, Classification and Regression Tree (CART) analysis, and logistic regression. Only 31.6 % of VNSs had implemented a BCP, while 62.8 % planned to implement one by the end of March 2024. CART analysis identified smaller organizational scale and lower risk perception as key predictors of BCP absence: specifically, fewer clients, fewer full-time equivalent (FTE) nurses, and lack of experience with natural hazard-induced disasters (NHIDs). Logistic regression confirmed that fewer FTE nurses were significantly associated with BCP absence (OR = 0.87, 95 % CI 0.78–0.97; p = 0.02). To promote universal implementation, targeted support is needed for small-scale VNSs and for enhancing risk perception. Flexible, scalable tools and regional collaboration may help strengthen both the adoption and operationalization of BCP—particularly through regular reviews, training, and simulation exercises. •Only 31.6 % of Japanese visiting nurse stations had a BCP before the national mandate in 2024.•CART analysis identified small organizational size and lower risk perception as key predictors of BCP absence.•Fewer clients, fewer full-time equivalent nurses, and absence of disaster experience were associated with non-implementation.•To ensure universal implementation, risk awareness and resource-sensitive support are essential.